Aplikasi Booking online Berbasis Website dengan Metode TOPSIS pada CV Titan Jaya Travelindo - Jasurjon Mirzoev; Meivi Kusnandar; Henny Madora (KERNEL: Jurnal Riset Inovasi Bidang Informatika dan Pendidikan Informatika, 2026)
CV Titan Jaya Travelindo (Titan Travel) is a travel agency in Palembang offering domestic and international Tour packages. The existing semi-conventional booking process via phone, WhatsApp, and direct counter visits causes booking backlogs, manual recording errors, the absence of an intelligent recommendation system, and difficulties in real-time financial monitoring. This study builds an integrated website-based online booking application using the Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) as a smart recommendation engine, developed with the Waterfall methodology using Next.js and MySQL. TOPSIS evaluates packages on four criteria: ticket price (weight 35%, Cost), vehicle/hotel facilities (weight 25%, Benefit), departure time (weight 20%, Cost), and travel duration (weight 20%, Cost). Applied to five alternatives, TOPSIS ranked the Palembang–Yogyakarta 2D1N Domestic Package first with a relative preference value (Vi) of 0.6177, while the Singapore 3D2N International Package ranked last with Vi = 0.3456. Blackbox Testing across 16 scenarios yielded a 100% pass rate, confirming full compliance with functional specifications.